RELATIONSHIP BETWEEN RATE OF FEEDING, GROWTH AND CONVERSION IN MAJOR INDIAN CARPS - Sen, P R; Rao, N G S; Mohanty, A N (Indian Journal of Fisheries, 2011)
Feed experiroemts conducted with a mixture of rice polish and groundnut oilcake mixed in equal proportions by weight at rates equivalent to 1, 2. 3, 4, 5 and 6 parcent of the initiali body weight of the carps fingerlings show that in rohu, growth and oonveisdon rates were best at 5 percent treatment, in the temperature range of 16.2Â°-26.0Â° C. In mrigal, though 6 percent level of feeding recorded maximum growth, the ’best conversion was obtained at 5 percent level in the temperature range of 23.2Â° to 30.0Â°C. This appears to suggest that higher rates of feeding above the level equivalent to 5 percent of the initial body weight may not be useful. The maintenance level of mrigal was observed to be more than of rohoi.